A ratiometric flavone-based fluorescent probe for hypochlorous acid detection with large Stokes shift and long-wavelength emission. (July 2019) - He, Long; Zhang, Yun; Xiong, Haiqing; Wang, Jingpei; Geng, Yani; Wang, Benhua; Wang, Yangang; Yang, Zhaoguang; Song, Xiangzhi
Abstract: A ratiometric fluorescent probe, FPT, was designed and synthesized for the selective and sensitive detection of hypochlorous acid (HClO) based on a flavone derivative under a single wavelength excitation. The addition of HClO to the solution ofFPT induced a distinct fluorescence color change from orange to green. ProbeFPT was successfully used to detect and image intracellular HClO in living zebra fish in a ratiometric manner. Graphical abstract: A flavone-based ratiometric fluorescent probe with large Stokes shift and long-wavelength emission for the sensitive and selective detection of hypochlorous acid has been developed. The application of this probe for imaging hypochlorous acid in zebra fish was successfully demonstrated under a single-wavelength excitation.Image 1 Highlights: This probe had large Stokes shift. This probe displayed a ratio fluorescence I524 nm /I586 nm with a single-wavelength excitation at 380 nm. This probe had long-wavelength emission.